Evaluation of seismic performance of precast concrete walls with X-shaped steel plate bracings. (February 2023) - Liu, Zelong; Wang, Mengfu; Samuel Hogan, Lucas
Abstract: Structures utilizing precast concrete walls have wide usage around the world, yet previous earthquakes have revealed the seismic performance of those walls is often deficient. These deficiencies can result in shear sliding at the wall base or brittle shear failure of the wall. These failure modes have been shown to be suppressed through the use of diagonal reinforcement in cast-in-situ walls, however, the tolerances and reinforcement geometry make the use of diagonal reinforcement in precast walls very difficult to achieve. In this paper, as an alternative to traditional diagonal reinforcement, X-shaped steel plate bracing was adopted in precast concrete walls and connected with welded joints. The experimental tests of four walls are presented, all of which incorporated the bracing and used either a cast-in-situ or bolted steel connection. The influence of the foundation connection and X-shaped steel plate bracing on the seismic performance of walls with different shear span ratios is described. The X-shaped steel plate bracing was found to effectively control shear sliding, with a greater decrease in shear sliding for walls with a lower shear span ratio. The bracing improved the peak strength of the walls, but the improvement varied with the angle of the bracing. The precast concrete walls with X-shaped steel plate bracing performed similar flexural failure modes to the reinforced concrete walls with a low shear span ratio but formed a plastic zone at the mid-height of the wall panel for the precast wall with a shear span ratio of 2.282. Numerical models developed for the precast concrete walls were able to estimate the force-displacement relationships.